The Impact of Organization Citizenship Behavior on Quality Service in Padang Restaurant Jakarta - Aripin; Juhary, Ali (2023)
The purpose of this study is to explain the effect of organization Citizenship Behavior on service quality at Padang restaurants in the Jakarta area. The method used is a quantitative approach. In this research, there are 18 Padang cuisine restaurants have participated. Each restaurant is represented by 12 employees so that the population is 216 people and then calculated using the Slovin formula with an error limit of 0.05 so that the sample has 140 employees. After being distributed, it turned out that the questionnaires returned 120 questionnaires. Data analysis using smart PLS-3 software. The results of the study show that OCB which is reflected by Altruism , Awareness , Courtesy and Loyalty proven to be able to improve the quality of service.